The Liberal Democrat Party : From Contender to Coalitionist - Muriel Cassel-Piccot (Revue LISA)
This research paper examines the progress the Liberal Democrats have achieved since 1988 and assesses the role they have carved for themselves on the British political stage. After a brief reminder of how the party came into being, and then both preserved and developed a specific political tradition, the way its core values are applied is considered. Special attention is devoted to the identity and workings of the party, and more particularly its federalist and democratic approach. The strategies pursued have led the organisation to success. However, they have also involved a professionalization of the group that has produced tensions, which the various leaders, in their own different styles (a visionary strategist, a communicative integrator, a reliable caretaker and an ambitious negotiator), have tried to ease. The task of the party today is all the more difficult as, while sharing power with the Conservatives, they have to keep on defending an “average” position, which often entails paradoxes and compromises – features that are not consistent with the adversarial nature of British politics.